The Antioxidant Activity of Red Fruit Juice (Pandanus conoideus Lam.) Using The FRAP Method - Ainunnisa, Mufti; Fawwaz, Muammar; Pratama, Mamat (Universitas Muslim Indonesia, 2025)
Red fruit is a member of the Pandanaceae family which is a type of pandan. Empirically, red fruit (Pandanus conoideus Lam.) has been proven to cure various degenerative diseases such as cancer, heart disease, tuberculosis, respiratory tract disorders, external antiseptic and eye and skin diseases. The aim of this research was to determine the antioxidant activity of red fruit juice using the ferric reducing antioxidant power (FRAP) method. The juice was tested qualitatively and quantitatively using the FRAP method. The qualitative test results after adding the FRAP reagent were positive for antioxidant activity because the color changed to blue. In quantitative determination of absorbance, antioxidant activity was measured using the UV-Vis spectrophotometric method. Absorbance was measured at a maximum wavelength of 701 nm using ascorbic acid as a reference solution. The equation obtained is y = 0.0103x + 0.3801 with a value of r = 0.9978. The total antioxidant activity value was calculated based on absorption data. The calculation results for the total antioxidant activity value were 173.68 mgAAE/L sample. Therefore, we can conclude that red fruit can be used as a natural antioxidant.